2017
DOI: 10.1515/cttr-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Smoking Questionnaire

Abstract: SUMMARYThe smoking questionnaire (SQ), a multidimensional questionnaire covering the major dimensions of cigarette smoking, was developed to address the heterogeneity in the assessment of smoking exposure. It consists of eight questions and can be completed within a few minutes. Test-retest reliability of the SQ and concurrent validity with the Behavior Risk Factor Surveillance System (BRFSS) 2011 questionnaire were examined in a clinical study conducted in adult US current menthol cigarette smokers. The SQ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The Smoking Questionnaire, included in the ABOUT™ Toolbox, was developed to provide a core set of questions that cover the major dimensions of TNP use and is consistent with criteria used for defining smoking history and status 51 . It assesses frequency and intensity of current and past TNP use behavior, initiation, and cessation and demonstrates good test-retest reliability 52 , 53 .…”
Section: Resultsmentioning
confidence: 99%
“…The Smoking Questionnaire, included in the ABOUT™ Toolbox, was developed to provide a core set of questions that cover the major dimensions of TNP use and is consistent with criteria used for defining smoking history and status 51 . It assesses frequency and intensity of current and past TNP use behavior, initiation, and cessation and demonstrates good test-retest reliability 52 , 53 .…”
Section: Resultsmentioning
confidence: 99%
“…Part 1 comprises a multidimensional Smoking Questionnaire (SQ) [38,39], which was developed to standardize the assessment of cigarette smoking exposure covering the major dimensions of cigarette smoking. SQ is used to assess cigarette smoking history and behavior.…”
Section: Methodsmentioning
confidence: 99%
“…SQ is used to assess cigarette smoking history and behavior. Test-retest reliability of the SQ and concurrent validity with the Behavior Risk Factor Surveillance System 2011 questionnaire have demonstrated that the SQ is reliable and easy to use [39]. Most importantly, the information collected using SQ allows for classification of smoking behavior and history according to the World Health Organization (WHO) definitions [40].…”
Section: Methodsmentioning
confidence: 99%